Case report: An autopsy report of patient with metastatic brain tumor and carcinomatous meningitis mimicking paraneoplastic neurological syndrome - Amano, Ryota; Sunouchi, Azusa; Yokota, Yuka; Mochizuki, Kunio (Frontiers in Neurology, 2024)
Differential diagnosis of metastatic brain tumor, carcinomatous meningitis, and paraneoplastic neurological syndrome (PNS) can be challenging in atypical cases. When examining patient with increased T2 fluid-attenuated inversion recovery (FLAIR) hyperintensities in the temporal polar white matter, autoimmune encephalitis, including PNS, should be considered. Herein, we report the case of an 85-year-old man with carcinomatous meningitis due to lung large cell carcinoma. He showed disturbance of consciousness, abnormal behavior, incomprehensible speech, and apathy, which suggested brain dysfunction. Magnetic resonance imaging revealed high intensities on the whole cerebellum on a diffusion-weighted image and bilateral T2 FLAIR hyperintensities in the temporal polar white matter. Cerebrospinal fluid analysis and cytology showed elevated total protein levels, pleocytosis, and atypical cells with nuclear enlargement, hyperchromasia, and irregular shape. Autopsy revealed lung large cell carcinoma and its brain metastasis. Tumor cells were disseminated to the central nervous system along the subarachnoid space. Furthermore, plenty of carcinoma cells and peritumoral enlarged perivascular space were observed in the temporal poles. To our knowledge, this is the first report of bilateral T2 FLAIR hyperintensities in the temporal polar white matter caused by carcinomatous meningitis with pathological confirmation. In patient with carcinomatous meningitis, abnormal T2 FLAIR hyperintensities may not be derived from ischemia or tumor invasion to parenchyma.